Augmented Reality as a Bridge between Culture and Technology in Mathematics Education: A Meta-Analysis - Maximus Tamur; Eliterius Sennen; Princess De Guzman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The rapid development of Augmented Reality (AR) in education has created new possibilities for connecting cultural heritage with technological innovation, particularly through an ethnomathematics approach to mathematics learning. This study provides novelty by offering a comprehensive meta-analysis investigating how sample size and subject matter moderate the effectiveness of AR-based ethnomathematics in improving mathematics education outcomes. Fifteen relevant empirical studies published between 2015 and 2025 were systematically identified through leading academic databases, and effect sizes were synthesized using a random-effects model. A rigorous coding process and statistical analysis were used to ensure the reliability and validity of the findings. The results indicate that AR significantly improves students' mathematical abilities, with variations depending on the subject matter. Furthermore, subject matter was found to be an important moderating variable, influencing the extent to which AR supports the integration of cultural and technological dimensions in mathematics education. These findings recommend that future research consider pedagogical design, cultural context, and technological adaptability when implementing AR-based ethnomathematics to optimize learning outcomes.